The crime rate and income inequality in Brazil: a nonlinear ARDL approach - Goh, Lim Thye; Law, Siong Hook (Inderscience, 2022)
This paper explores the relationship between the crime rate and income inequality for Brazil using a nonlinear autoregressive distributed lag (NARDL) model. Our result suggests that the crime rate and income inequality are significantly cointegrated. Besides, the NARDL model affirms the presence of asymmetric behaviour between the crime rate and income inequality. More specifically, in the long run, reduced income inequality will lead to a decrease in the crime rate with a greater deviation, whereas an increase in income inequality tends to lead to an increase in the crime rate with a lower deviation. Therefore, the crime rate responds more to negative changes than to positive changes in the level of income inequality.